Comparison of multiple monitoring techniques for the testing of a scale model timber Warren truss - Henry Helmer-Smith; Nicholas Vlachopoulos; Marc-André Dagenais; Bradley Forbes (Canadian Science Publishing, 2021)
This paper outlines the testing and monitoring procedure of a scale model Warren truss constructed of 2 inch × 4 inch (38 mm × 89 mm) members and bolted connections within a laboratory environment. Several forms of deflection monitoring and strain monitoring instrumentation were utilized throughout this laboratory testing phase of a longer-term research program. Instruments included: an automatic total station, linear variable differential transducers, light detection and ranging, electric strain gauges, and distributed optical fibre sensors. The distributed point load-testing regime included two configurations: (i) the original truss configuration and (ii) the installation of intermediate columns beneath the truss. Objectives of this phase included identifying instrument capabilities, limitations, and overall reliability/effectiveness with respect to representing the behaviour of the truss system. In addition, members of interest and critical monitoring locations along the Warren truss were determined. The purpose of this laboratory endeavour was to determine an optimized structural-health monitoring program prior to implementation in a heritage timber Warren truss structure within the infrastructure inventory of the Department of National Defence (DND). An options analysis of monitoring techniques was conducted whereby the effectiveness of each instrumentation type was evaluated according to relevant metrics/factors to determine an effective monitoring technique for this heritage building and other similar DND truss structures.